Direct Pellet PCR: Rapid Extraction-Free Method for Identification of Cellulolytic Bacteria from Empty Fruit Bunch - Pamungkas, Edo Agam; Madusari, Sylvia; Putri, Halida Adistya; Rosita, Risa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Oil Palm (Elaeis guineensis Jacq.) is a major industrial crop producing large amounts of empty fruit bunches (EFB), which necessitate rapid molecular methods to support microbial biodiversity studies and biotechnology applications. This study evaluated the effectiveness of Direct Pellet PCR as a rapid, extraction-free method for the molecular identification of cellulolytic bacteria isolated from EFB. Bacterial cell pellets were directly used as PCR templates to amplify the 16S rRNA gene without prior DNA extraction. The method consistently produced clear and specific amplicons of approximately 1500 bp for all isolates, indicating reliable PCR amplification. Sequence analysis showed similarity values ranging from 68.82% to 80.43% compared with reference sequences in the NCBI database, suggesting low similarity to currently available references. These findings demonstrate that Direct Pellet PCR is an efficient and cost-effective approach for rapid DNA amplification and preliminary molecular screening of cellulolytic bacteria from lignocellulosic substrates.